First record of Vigna vexillata (Fabaceae, Faboideae) for Sinaloa, Mexico - Amador-Cruz, Francisco; Benítez Pardo, Daniel; Briseño Dueñas, Raquel (Instituto de Ecología, A.C., 2017)
Background and Aims: The Flora of Sinaloa consists of 3736 species; however, the knowledge of it is scarce. Most of the studies have been carried out in the northern portion, whereas the present work was developed in the south zone. The objective is to contribute to the knowledge of this flora, through a new record of the species Vigna vexillata at state level.Methods: Throughout the study area, five field trips were carried out, during which plants were collected, following the recommendations for the preparation of botanical specimens; these were determined with specialized taxonomic bibliography.Key results: A taxon of the genus Vigna was determined, which to date was not reported for the flora of Sinaloa. It is recognized for presenting the keel turn to left, cordate stipules, terete and linear fruit, and brown pubescence. The species was collected in the Escuinapa coastal area. This record extends the distribution of the species to a more northern area.Conclusions: This record suggests the need to continue observing the flora in the south area of the state of Sinaloa, since it is scarcely studied and presents a great variety of types of vegetation, which have remained unexplored.